The Use of Prebiotic and Organic Minerals in Rations for Japanese Laying Quail - Costa, Fernando Guilherme Perazzo; Nobre, I.S.; Silva, L.P.G.; Goulart, C.C.; Figueiredo, D.F.; Rodrigues, V.P. (International Journal of Poultry Science, 2008)
The aim of this research was to evaluate the effects of prebiotics and organic minerals usage upon both the productive performance and the eggs internal and external quality of quail. 300 Japanese laying quails (Coturnix coturnix japonica) was used, from 13 to 28 weeks of age, distributed in a completely randomized design, with five treatments and six replicates and 10 quails per experimental unit. Treatments consisted in T1 - Control (neither Bio-Mos nor Bioplex Repro), T2 (0.5 kg/ton Bio-Mos), T3 (1.0 kg/ton Bio-Mos), T4 (0.5 kg/ton Bio-Mos + 1.0 kg/ton Bioplex Repro and T5 (1.0 kg/ton Bio-Mos + 1.0 kg/ton Bioplex Repro). It was not verified effect of the treatments on the weight of eggs, feed conversion by egg dozen and feed conversion by egg mass. Notwithstanding, feed intake, egg production and mass were influenced, being the best production and egg mass (79.8% and 10.2 g/bird/day, respectively) observed under a diet containing 0.05% of Bio-Mos (prebiotic) to Japanese laying quails.